ANALISIS PENERAPAN PEMOTONGAN PAJAK PENGHASILAN PASAL 26 ATAS DIVIDEN WAJIB PAJAK LUAR NEGERI DI PERUSAHAAN PERBANKAN - Diva Alexsa Putri; Suci Novia Audira; Cahaya Fadillah (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the implementation of Income Tax (PPh) Article 26 withholding on dividends paid to Foreign Taxpayers (WPLN) in banking companies. The research employs a literature review approach, examining empirical data and tax theories related to the process of withholding, depositing, reporting, and the administration of supporting documents such as the DGT Form and Certificate of Residence (CoR). The results indicate that although the withholding and depositing mechanisms of Article 26 Income Tax in banking companies, particularly at PT Bank Pembangunan Daerah Jawa Timur, have generally complied with regulations, challenges remain in reporting and document completeness. Incomplete documentation leads to the application of the default 20% tax rate and poses risks of sanctions and reduced confidence from foreign investors. Key factors influencing compliance include the understanding of tax staff, outreach to foreign taxpayers, and the integration of administrative systems. This study recommends strengthening administrative systems, enhancing education, and fostering collaboration between tax authorities, banks, and foreign taxpayers to improve the effectiveness and compliance of Article 26 Income Tax implementation and to support the optimization of state revenue.